2011
DOI: 10.1016/j.bbmt.2010.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Novel H1N1 Influenza in Hematopoietic Stem Cell Transplantation Recipients: Two Centers’ Experiences

Abstract: Respiratory virus infections, such as influenza A, cause significant morbidity in hematopoietic stem cell transplantation (HSCT) recipients. The clinical characteristics and impact of infection with the novel H1N1 virus in this patient population is not yet well defined, however. HSCT recipients diagnosed with proven or probable H1N1 during the 2009 pandemic were identified and charts were retrospectively reviewed with analysis of clinical descriptions, risk factors, diagnosis, treatments, and outcomes. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
36
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
8
36
2
Order By: Relevance
“…Moreover, the disease severity of 2009 H1N1 compared with seasonal influenza was not described. In our cohort, the proportion of LRD, hypoxemia, mechanical ventilation, and deaths in HCT patients with 2009 H1N1 was higher than those reported by Redelman-Sidi et al 30 and Cost et al 35 as well as those in solid-organ transplant recipients, 36 but consistent with the recent report by Taplitz et al 7 At the beginning of the pandemic, many experts, agencies, and transplant societies recommended that transplant recipients with pandemic H1N1 should be started on antiviral treatment regardless of symptom duration or even definitive diagnosis, and that combination antiviral therapy and high-dose oseltamivir could be considered for LRD. 5,37 We used a higher dose of oseltamivir (150 mg, twice daily) because of the questionable absorption in patients with GVHD-associated malabsorption, as well as the higher viral load and prolonged shedding in HCT recipients.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Moreover, the disease severity of 2009 H1N1 compared with seasonal influenza was not described. In our cohort, the proportion of LRD, hypoxemia, mechanical ventilation, and deaths in HCT patients with 2009 H1N1 was higher than those reported by Redelman-Sidi et al 30 and Cost et al 35 as well as those in solid-organ transplant recipients, 36 but consistent with the recent report by Taplitz et al 7 At the beginning of the pandemic, many experts, agencies, and transplant societies recommended that transplant recipients with pandemic H1N1 should be started on antiviral treatment regardless of symptom duration or even definitive diagnosis, and that combination antiviral therapy and high-dose oseltamivir could be considered for LRD. 5,37 We used a higher dose of oseltamivir (150 mg, twice daily) because of the questionable absorption in patients with GVHD-associated malabsorption, as well as the higher viral load and prolonged shedding in HCT recipients.…”
Section: Discussionsupporting
confidence: 43%
“…31 Taplitz et al showed that 52% of 27 patients with 2009 H1N1 had LRD, half of them required mechanical ventilation, and the overall influenza-associated mortality was 22%. 7 The reported number of patients in each of these and other recent reports [32][33][34] is relatively small, and the clinical outcomes of 2009 H1N1 vary somewhat differently in the different reports. Moreover, the disease severity of 2009 H1N1 compared with seasonal influenza was not described.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Pandemic H1N1 (2009) influenza A infections may lead to severe pneumonia in children and young adults, with immunosuppression being an important risk factor [3][4][5]. Due to the profound immunodeficiency in patients after alloHSCT, pandemic H1N1 (2009) influenza A infection causes more severe respiratory disease in HSCT recipients than seasonal influenza A and B viruses, with graft-versus-host disease (GvHD) being an additional risk factor [6][7][8][9][10]. Therefore, prevention and prophylaxis of infections, including re-vaccination, are crucial in this patient group [11].…”
Section: Introductionmentioning
confidence: 99%
“…Outcome of 27 cases of 2009H1N1 was examined in a study from two centers after HCT. 42 Influenzarelated 30-day mortality was 22% overall, but patients with lower respiratory tract infection (LRTI) had a 43% mortality rate. Progression from upper tract to lower tract disease therefore has an important impact on mortality.…”
mentioning
confidence: 99%